Physical properties and applications of polymer nanocomposites - Tjong, Sie Chin; Mai, Y. W., 1946- (Woodhead Publishing in materials., 2010)
Polymer nanocomposites are polymer matrices reinforced with nano-scale fillers. This new class of composite materials has shown improved mechanical and physical properties. The latter include enhanced optical, electrical and dielectric properties. This important book begins by examining the characteristics of the main types of polymer nanocomposites, then reviews their diverse applications. Part one focuses on polymer/nanoparticle composites, their synthesis, optical properties and electrical conductivity. Part two describes the electrical, dielectric and thermal behaviour of polymer/nanoplatelet composites, whilst polymer/nanotube composites are the subject of Part three. The processing and industrial applications of these nanocomposite materials are discussed in Part four, including uses in fuel cells, bioimaging and sensors as well as the manufacture and applications of electrospun polymer nanocomposite fibers, nanostructured transition metal oxides, clay nanofiller/epoxy nanocomposites, hybrid epoxy-silica-rubber nanocomposites and other rubber-based nanocomposites. Polymer nanocomposites: Physical properties and applications is a valuable reference tool for both the research community and industry professionals wanting to learn about the these materials and their applications in such areas as fuel cell, sensor and biomedical technology. Examines the characteristics of the main types of polymer nanocomposites and reviews their diverse applicationsComprehensively assesses polymer/nanoparticle composites exploring experimental techniques and data associated with the conductivity and dielectric characterizationA specific section on polymer/nanotube composites features electrical and dielectric behaviour of polymer/carbon nanotube composites.